The Relationship Between Maternal Anxiety and Basic Immunization in Toddlers - syafaati, Aditya Laily; Supatmi, Supatmi; Yumni, Fathiya Lutfil; Mukarromah, Nur (Indonesian Academia Health Sciences Journal, 2022)
There is still a lot of anxiety experienced by mothers in giving immunizations to. So, it is common to give incomplete immunizations to children. Factors that often influence maternal anxiety in giving immunizations are behavioral views, interpersonal views, age, gender, educational status, and occupation. This research is conducted to analyze the correlation between maternal anxiety and giving basic immunization to toddlers in Sedayulawas Village, Brondong District. This research uses correlation analytic research methodology with cross sectional approach. The population is 57 mothers in Sedayulawas Village, Brondong District and the sample is 50 respondents selected by consecutive sampling technique. The independent variable is anxiety and the dependent variable is basic immunization. The research data are collected within 3 weeks using the HARS questionnaire and the MCH handbook. The data are analyzed using Spearman Rank Test correlation test with p˂0.05. The results of this research indicate that the no anxiety level shows percentage of 38.0% or 19 respondents. Basic immunization is mostly complete with a percentage of 52.0% or 26 respondents. The results of the analysis show that there is a correlation between maternal anxiety and giving basic immunization in Sedayulawas Village, Brondong District (p = 0,000 ˂ α 0,05 with the correlation value of 0.780). It means that there is a strong correlation between maternal anxiety and basic immunization for toddlers in Sedayulawas Village, Brondong District. Conclusion of the research: There is a strong correlation between maternal anxiety and giving basic immunization to children under five-year-old in Sedayulawas Village, Brondong District. Therefore, mothers who have toddlers need to participate in health education regarding complete basic immunization and ask a lot of questions before giving immunizations.